Travel solutions system / Ariati Karina khalid - Ariati Karina, Khalid (2004)
The present paper will outline the creation and evaluation of a tourism destination advisory system named Travel Solutions. Advisory system became a significant tool in the field of tourism; they offer users a convenient opportunity to find a travel bundle or a single travel item such as accommodation. Existing tourism destination advisory system has some shortcomings as they allow no or only very limited flexibility when taking constraints or preferences into account. Therefore, the aim to design a novel type of advisory system including features of Case-Based Reasoning (CBR) will be pursued. The system enables the selection of travel locations and supports the bundling of personalized travel plan. Travel plans are stored in a memory cases, which exploited for ranking travel items extracted from knowledge base. Knowledge intensive session modeling and mixed initiative advisor are introduced in the CBR framework. The application of these ideas to an interactive, case-based tourism destination advisory system, that guides traveler' decision making processes, is described.